The Paradox of Emerging Technologies in Playing Fundamental Role on Administration Employee’s Roles and Responsibilities - Mogale, R. J.; Mkhomazi, S. S.; Rankhumise, R. M. (Journal of Economics and Behavioral Studies, 2018)
This article aims to put forward the imperatives of emerging technologies in playing fundamental role on administration work effectiveness and efficiency. The nature of office work has changed through time due to the emergence of new technologies that are adopted and implemented in the government departments. The emerging technologies are the heartbeat of any organisation and simultaneously they are the structure and thread holding it all together. With this study, a survey design was adopted and data collection was done through structured questionnaire. The study argues that the influx of emerging technologies increases the relationship with stakeholders and shareholders, responsiveness, transparency and accessibility of quality service delivery. This has resulted in government departments enhancing the effective communication between government and citizens, while it creates opportunities for government employees. Therefore, the study concludes that with the emergence of technologies, it is important for government departments to initiate new technologies in the departments to faster transactions, provide excellent service delivery to citizens of South Africa and as well as improving mass communication.